2007
DOI: 10.1177/0017896907080120
|View full text |Cite
|
Sign up to set email alerts
|

Health promotion intervention for hygienic disposal of children's faeces in a rural area of Nigeria

Abstract: Objective Community-based health promotion intervention for improving unhygienic disposal of children's faeces was conducted in a rural area of Nigeria. Setting The study was conducted in Ife South Local Government area of Osun State, Nigeria. Design The study was conducted in 10 randomly selected rural villages: five control and five active. Method The intervention, which lasted for nine months, consisted of hygienic use of chamber-pots for the disposal of children's faeces, discouraging children from defe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(38 citation statements)
references
References 4 publications
1
37
0
Order By: Relevance
“…In Hoque et al (1994/1996) it was shown that latrine use after the intervention increased by 89%, however no standard deviations were provided, so it was not possible to calculate confidence intervals. Adherence outcomes were measured in two different experimental studies, describing a sanitation only intervention, and a significant increase in overall latrine use (RR 2.59, 95% CI [1.58, 4.25]), and latrine use in children up to 24 months (RR 7.95, 95% CI [4.72, 13.40]) was shown (Pattanayak et al, 2009; Jinadu et al, 2007), however no difference in latrine use in children between 25 and 60 months could be shown (RR 4.74, 95% CI [0.24, 95.33]) (Jinadu et al, 2007). The adherence outcomes had a low certainty of evidence (Table 20).…”
Section: Results: Effectiveness Of Different Approachesmentioning
confidence: 99%
See 3 more Smart Citations
“…In Hoque et al (1994/1996) it was shown that latrine use after the intervention increased by 89%, however no standard deviations were provided, so it was not possible to calculate confidence intervals. Adherence outcomes were measured in two different experimental studies, describing a sanitation only intervention, and a significant increase in overall latrine use (RR 2.59, 95% CI [1.58, 4.25]), and latrine use in children up to 24 months (RR 7.95, 95% CI [4.72, 13.40]) was shown (Pattanayak et al, 2009; Jinadu et al, 2007), however no difference in latrine use in children between 25 and 60 months could be shown (RR 4.74, 95% CI [0.24, 95.33]) (Jinadu et al, 2007). The adherence outcomes had a low certainty of evidence (Table 20).…”
Section: Results: Effectiveness Of Different Approachesmentioning
confidence: 99%
“…Elements of psychosocial theory Andrade, 2013Guiteras et al (2015bHuda et al, 2012Jinadu et al, 2007Kochurani et al, 2009Patil et al, 2013Pattanayak et al, 2009Phuanukoonnon et al, 2013Pickering et al, 2015Waterkeyn & Cairncross, 2005) Younes et al, 2015Arnold et al, 2009Biran et al, 2009Briceno et al, 2015Cameron et al, 2013Dickey et al (2015) Galiani et al, 2012Pinfold, 1999Abiola et al, 2012Bowen et al, 2013Caruso et al, 2014Graves et al (2011) Guiteras et al (2015a) Kaewchana et al, 2012Lansdown et al, 2002Mascie-Taylor et al, 2003Pickering et al, 2013Seimetz et al, 2016Wang et al, 2013Zhang et al (2013 Figure 6 also lists the specific approach in each study and the WASH component for each study.…”
Section: Social Marketing Approach Sanitation and Hygiene Messagingmentioning
confidence: 99%
See 2 more Smart Citations
“…Educational and behaviour change interventions have been tested for improving child defecation and faeces disposal practices and, although they can be successful , many have failed to show sustained improvement in child defecation or faeces disposal practices . Recent work suggests that reusable diapers and child potties may be helpful for promoting safe child faeces management as well as improving local tools for picking up child faeces ; however, there is not yet evidence from completed trials regarding the success of these enabling products.…”
Section: Discussionmentioning
confidence: 99%